1984
DOI: 10.1021/bi00299a009
|View full text |Cite
|
Sign up to set email alerts
|

Active-site mapping of bovine and human blood coagulation serine proteases using synthetic peptide 4-nitroanilide and thio ester substrates

Abstract: A series of 14 tripeptide 4-nitroanilide substrates of the type Z-AA-Gly-Arg-NA and Z-AA-Phe-Arg-NA where AA = Ala, Asn, Glu, Lys, Phe, Pro, or Ser were used to map the S3 subsite of several serine proteases involved in blood coagulation. The enzymes studied included bovine thrombin, factor IXa, factor Xa, factor XIa, human beta-factor XIIa (factor XIIa fragment), and activated bovine and human protein C. Kinetic constants (kcat, KM, and kcat/KM) for the enzymatic hydrolysis of the substrates by each enzyme we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 34 publications
5
46
0
Order By: Relevance
“…2a). The P2-Gly was most effective as previously reported [7,24,26,35,361, resulting in the increase of the k,,, value. In addition, the Gly and Ala residues contributed to increase the l/Km value.…”
Section: Bovine Factor Xasupporting
confidence: 70%
See 4 more Smart Citations
“…2a). The P2-Gly was most effective as previously reported [7,24,26,35,361, resulting in the increase of the k,,, value. In addition, the Gly and Ala residues contributed to increase the l/Km value.…”
Section: Bovine Factor Xasupporting
confidence: 70%
“…In contrast, the peptide-NH-Mec substrates with a Phe residue at the P2 site were less reactive. Stone and Hofsteenge [33] and Cho et al [24] also reported that a-thrombin cleaves poorly peptide-p-nitroanilide substrates with a Phe residue at the P2 site. On the other hand, McRae et al [26] have found that the P2-Phe derivative is a good substrate for a-thrombin, using peptide thioesters.…”
Section: Human A-thrombinmentioning
confidence: 97%
See 3 more Smart Citations